Kolaborasi Guru-Orang Tua di RA Al-Manshuriyah: Menelisik Bentuk, Kendala, dan Potensi Penguatan Dukungan Perkembangan Anak Usia Dini - Nurhasanah, Santi; Rodiah, Iis; Nuraida, Nia (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2026)
Early Childhood Education (PAUD) plays a fundamental role in shaping an individual's holistic development, encompassing cognitive, physical-motor, socio-emotional, language, and character and moral values. The success of PAUD relies heavily on the synergy between two key ecosystems: the family and the educational institution. However, in practice, collaboration between these two parties often faces challenges, such as role perception gaps and suboptimal communication, which can hinder a child's development. The Independent Curriculum policy increasingly emphasizes the active role of families, but its implementation remains hampered by parents' limited time and a vague understanding of the partnership's scope. This study aims to explore and analyze in depth the dynamics of the teacher-parent partnership at RA Al-Manshuriyah. Using a qualitative case study design, the research involved in-depth interviews with teachers, parents, and the principal, as well as participant observation and documentation. Data analysis was conducted through data reduction, data presentation, conclusion drawing, and verification. The research findings are expected to map the forms of collaboration implemented, identify stakeholders' perceptions of their effectiveness and benefits, and uncover the driving factors and obstacles encountered. The results of this study are expected to provide concrete recommendations to strengthen synergistic, sustainable partnerships that support optimal early childhood development at RA Al-Manshuriyah and similar institutions.